Level of overweight and obesity surpassed underweight among women in 40 low and middle-income countries: Findings from a multilevel multinomial analysis of population survey data - Kusse Urmale Mare; Kebede Gemeda Sabo; Beriso Furo Wengoro; Begetayinoral Kussia Lahole (PLoS ONE, 2025)
Background Despite continued global and local initiatives to address nutritional problems, low- and middle-income countries are facing both malnutrition and non-communicable diseases, with about 80% of non-communicable disease-related deaths. There is a dearth of recent evidence on the extent and determinants of underweight, overweight, and obesity in this region, which is essential for guiding intervention programs. Thus, this study intended to provide insights into the current level of malnutrition among women of reproductive age in low- and middle-income countries. Methods A secondary analysis of Demographic and Health Survey data from 40 low- and middle-income countries was performed using a weighted sample of 1,044,340 women of reproductive age. Forest plots and line graph were used to present the pooled and regional estimates of underweight and overweight and obesity. A multilevel multinomial logistic regression models were fitted to identify determinants of malnutrition and models were compared based on the deviance and log-likelihood values. In the final model, statistical significance was determined using an adjusted relative risk ratio with the corresponding 95% confidence interval. Results The overall prevalence of obesity and overweight was 26.8% (95% CI: 26.7%–26.9%), with the highest rate in Jordan (67.2%) and lowest in Burundi (9.5%). Additionally, the level of underweight was found to be 15.6% [95% CI: 15.5%–15.7%], ranging from 1.3% in Jordan to 25.4% in Timor-Leste. Women of families with middle and rich wealth indexes, those aged 25–34 and 35–49, contraceptive users, those with primary and higher education, and urban residents were more likely to be overweight or obese. In contrast, the results showed a lower likelihood of undernutrition among women in the households with middle [ARRR (95% CI): 0.83 (0.80–0.86)] and rich wealth indexes [ARRR (95% CI): 0.73 (0.71–0.76)], those with primary [ARRR (95% CI): 0.70 (0.68–0.73)], secondary [ARRR (95% CI): 0.71 (0.69–0.74)], and higher education [ARRR (95% CI): 0.57 (0.53–0.61))], and women with media access [ARRR (95% CI): 0.79 (0.77–0.82)]. Conclusion Over a quarter of women of reproductive age in LMICs were overweight or obese, with underweight affecting 15.6%. It was also found that the levels of overweight and obesity were higher than the rate for underweight, with wide variations across the countries. Thus, efforts to improve the modifiable risks can have a positive impact on reducing undernutrition and over-nutrition. Given the considerable variations between countries and survey periods, nutrition programs should also be tailored to the specific needs and cultural contexts of different regions within the study settings. Furthermore, the findings suggest the need for regular monitoring and evaluation of the existing nutritional interventions to assess their effectiveness.